Analisa Gaya Potong pada Proses Frais Komponen Kereta Api Menggunakan OCTAVE: Bagian 1 Up Milling - Agus Susanto; Indarto Yuwono; Noorsakti Wahyudi; Ramadhana Eka Wicaknono (Manutech : Jurnal Teknologi Manufaktur, 2021)
Milling is widely applied to process train components, especially for finishing wheel-set, boogie frames, and slotting shafts. The cutting forces of milling during operation is important to analyze because they affect on the final product. The analysis can be experimental data observation or simulation. This article presents simulation of cutting forces in up-milling with various input parameters using Octave open software. The simulation results showed that the exit angle (?e) was 80o and 60o for simulation 1 and simulation 2, respectively. The start angle (?s) was 0o for both simulation because it was up-milling process. Since the effective cutting angles were less than the interval angle of cutting edges (90o), only single cutting edge was involved in cutting. In addition, the cutting force was influenced by the cutting parameters, so that there were cutting force fluctuations during machining process. Differences in radial depth of cut, feed per tooth, and effective cutting angle affected in the differences of the cutting force quantity. In simulation 1, the resultant cutting force reached 400 N, while the cutting force Fx and Fy are 250 N and 325 N, respectively. In simulation 2, the resultant was 700 N, and 500 N and 420 N for Fx and Fy cutting forces, respectively. Spindle rotation speed did not affect on the quantity of cutting force but affects on the cutting time. In simulation 1 with a spindle speed of 7500 rpm, it took a cutting time of 0.008 seconds. While in simulation 2, the cutting time was slower, namely 0.012 seconds. This was because the spindle rotation speed reduced to 5000 rpm. The simulation also proved the characteristic frequency of milling process; tooth passing, and several harmonic frequencies.